HIV Clinical Pathway: A New Approach to Combine Guidelines and Sustainability of Anti-Retroviral Treatment in Italy. - Davide Croce; Adriano Lazzarin; Giuliano Rizzardini; Nicola Gianotti; Francesca Scolari; Emanuela Foglia; Elisabetta Garagiola; Elena Ricci; Teresa Bini; Tiziana Quirino; Paolo Viganò; Tiziana Re; et al. (PLoS ONE, 2016)
The present article describes the case study of a "real world" HIV practice within the debate concerning the strategic role of Clinical Governance (CG) tools in the management of a National Healthcare System's sustainability. The study aimed at assessing the impact of a Clinical Pathway (CP) implementation, required by the Regional Healthcare Service, in terms of effectiveness (virological and immunological conditions) and efficiency (economic resources absorption), from the budget holder perspective. Data derived from a multi-centre cohort of patients treated in 6 Hospitals that provided care to approximately 42% of the total HIV+ patients, in Lombardy Region, Italy. Two phases were compared: Pre-CP (2009-2010) vs. Post-CP implementation (2011-2012). All HIV infected adults, observed in the participating hospitals during the study periods, were enrolled and stratified into the 3 categories defined by the Regional CP: first-line, switch for toxicity/other, and switch for failure. The study population was composed of 1,284 patients (Pre-CP phase) and 1,135 patients (Post-CP phase). The results showed that the same level of virological and immunological effectiveness was guaranteed to HIV+ patients: 81.2% of Pre-CP phase population and 83.2% of Post-CP phase population had undetectable HIV-RNA (defined as <50 copies/mL) at 12-month follow up. CD4+ cell counts increased by 28 ± 4 cells/mm3 in Pre-CP Phase and 39 ± 5 cells/mm3 in Post-CP Phase. From an economic point of view, the CP implementation led to a substantial advantage: the mean total costs related to the management of the HIV disease (ART, hospital admission and laboratory tests) decreased (-8.60%) in the Post-CP phase (p-value < 0.0001). Results confirmed that the CP provided appropriateness and quality of care, with a cost reduction for the budget holder.